2017
DOI: 10.1177/0032258x17750325
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment experienced by police staff serving in England, Wales and Scotland: A descriptive exploration of incidence, antecedents and harm

Abstract: An on-line survey (N=1776) was conducted with support staff to explore both the type and incidence of sexual harassment within the police working environment and the explanatory value of known antecedent factors. Uni-variate results indicated highest levels of sexual harassment were associated with what has been termed sexual 'banter', reported by three quarters of those surveyed, with a diminishing level of exposure to more serious types of harassment. Respondents reported adverse impacts whether sexual haras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Due to a messaging error accompanying the PFEW survey which appeared to seek responses from women officers, only 18 policemen returned completed surveys. The number of returns from UNISON members is consistent with the Union's own survey returns (Brown et al, 2018;Unison, 2016). For the purpose of the present analysis, 437 women police officers and 1626 women police staff were selected from the total sample of 2844 (10 respondents were classified as other and six respondents declined to give their designation as staff or officer).…”
Section: Samplesupporting
confidence: 71%
“…Due to a messaging error accompanying the PFEW survey which appeared to seek responses from women officers, only 18 policemen returned completed surveys. The number of returns from UNISON members is consistent with the Union's own survey returns (Brown et al, 2018;Unison, 2016). For the purpose of the present analysis, 437 women police officers and 1626 women police staff were selected from the total sample of 2844 (10 respondents were classified as other and six respondents declined to give their designation as staff or officer).…”
Section: Samplesupporting
confidence: 71%
“…Reports and reviews such as those cited above have been supplemented by union wellbeing surveys and other documentation that provides information about police staff (Unison, 2003(Unison, , 2016. Police studies also add periodically to what we know about police staff (see e.g., Brown et al, 2018;McCarty & Skogan, 2013;Lumsden 2017). Other disciplines have looked specifically at 'civilian' or 'support' police staff (for example, managerial studies, Gwavuya, 2010;Dick & Metcalfe, 2001;Dick & Hyde, 2006).…”
Section: What Do We Know About Police Staff?mentioning
confidence: 99%
“…They also reported about their experiences in connection with adverse or hostile environments, sexism, skewed physical fitness assessments, double standards, boys club and lack of support & opportunity during their career. An online survey by Brown, Gouseti and Fife-Shaw on police staff serving in England, Wales and Scotland found that majority of harassment incidences (around 75 percent) were associated with sexual banter apart from exposure to severe types of harassment (Brown, Gouseti & Fife-Schaw, 2017). Many studies revealed the existence of varied forms of harassment in different professions, including law enforcement agencies.…”
Section: A) Nature Of Sexual Victimization Of Women In Police Professionmentioning
confidence: 99%